Study protocol for a multicentre randomised controlled trial: Safety, Tolerability, efficacy and quality of life Of a human recombinant alkaline Phosphatase in patients with sepsis-associated Acute Kidney Injury (STOP-AKI). Issue 9 (27th September 2016) - Peters, Esther; Mehta, Ravindra L; Murray, Patrick T; Hummel, Jürgen; Joannidis, Michael; Kellum, John A; Arend, Jacques; Pickkers, Peter
Abstract : Introduction: Acute kidney injury (AKI) occurs in 55–60% of critically ill patients, and sepsis is the most common underlying cause. No pharmacological treatment options are licensed to treat sepsis-associated AKI (SA-AKI); only supportive renal replacement therapy (RRT) is available. One of the limited number of candidate compounds in clinical development to treat SA-AKI is alkaline phosphatase (AP). The renal protective effect of purified bovine intestinal AP has been demonstrated in critically ill sepsis patients. To build on these observations, a human recombinant AP (recAP) was developed, of which safety and efficacy in patients with SA-AKI will be investigated in this trial. Methods: This is a randomised, double-blind, placebo-controlled, 4-arm, proof-of-concept, dose-finding adaptive phase IIa/IIb study, conducted in critically ill patients with SA-AKI. A minimum of 290 patients will be enrolled at ∼50 sites in the European Union and North America. The study involves 2 parts. Patients enrolled during Part 1 will be randomly assigned to receive either placebo (n=30) or 1 of 3 different doses of recAP (n=30 per group) once daily for 3 days (0.4, 0.8 or 1.6 mg/kg). In Part 2, patients will be randomly assigned to receive the most efficacious dose of recAP (n=85), selected during an interim analysis, or placebo (n=85). Treatment must be administered within 24 hours after SA-AKI is first diagnosed and within 96 hours from first diagnosis of sepsis. The primary end point is the area under the time-corrected endogenous creatinine clearance curve from days 1 to 7. The key secondary end point is RRT incidence during days 1–28. Ethics and dissemination: This study is approved by the relevant institutional review boards/independent ethics committees and is conducted in accordance with the ethical principles of the Declaration of Helsinki, guidelines of Good Clinical Practice, Code of Federal Regulations and all other applicable regulations. Results of this study will reveal the efficacy of recAP for the improvement of renal function in critically ill patients with SA-AKI and will be published in a peer-reviewed scientific journal. Trial registration number: NCT02182440; Pre-results.